Comparative Study on the in vitro Antibacterial Efficacy of Aqueous and Methanolic Extracts of Quercus infectoria Gall`s Against Cellulosimicrobium cellulans - Mustafa, Muskhazli; Y., Nurhafiza; Abd Aziz, Nor Azwady; E., Nor Dalilah (2008)
The in vitro antibacterial efficacy of aqueous and methanolic extract of Quercus infectoria Olivier (Fagaceae) galls was tested against Cellulosimicrobium cellulans using extract concentration ranging from 0.25 to 4 mg mL-1. Both types of extract showed significant inhibition of C. cellulans growth with strong correlation between extract concentrations and degrees of antibacterial activity for concentrations ranging from 0.5 to 4 mg mL-1. Although, slight reduction of average diameter of inhibition zones after 24 h of incubation for aqueous extract (0.96 ± 0.148 cm) compared to methanolic extract (1.00 ± 0.182 cm), both extracts still attained the MIC value beginning at a concentration of 0.5 mg mL-1 but established higher concentration for the MBC at 2 mg mL-1. The antibacterial activity of methanolic extract was also significantly affected by the temperature with an optimum inhibition zone being obtained at 30 °C (1.38 ± 0.05 cm) and this was reduced to approximately 20% at temperatures of above 50 °C.